2018
DOI: 10.1021/acsami.7b17187
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Nickel Phosphate Nano/Microflakes 3D Electrode for Electrochemical Energy Storage, Nonenzymatic Glucose, and Sweat pH Sensors

Abstract: Multifunctional, low-cost electrodes and catalysts are desirable for next-generation electrochemical energy-storage and sensor applications. In this study, we demonstrate the fabrication of Ni(PO)·8HO nano/microflakes layer on nickel foam (NF) by a facile one-pot hydrothermal approach and investigate this electrode for multiple applications, including sweat-based glucose and pH sensor as well as hybrid energy-storage device, e.g., supercapattery. The electrode displays a specific capacity of 301.8 mAh g (1552 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 71 publications
(153 reference statements)
1
71
0
Order By: Relevance
“…In contrast, most of the existing cobalt-based catalysts that are used for non-enzymatic sensing of Glu require strong alkaline conditions. 23,39,41,42 Furthermore, while some other metal phosphate systems (e.g., Ni 3 (PO4) 2 -based materials 66 ) have shown greater sensitivity for glucose detection than our currently reported materials, the detection range was investigated below the typical glucose concentration of human blood (i.e., <1 mM), and measurements were also performed in strongly alkaline conditions (1 M NaOH solutions). Figure S8 shows the amperometric responsiveness of commercial Co 3 (PO 4 ) 2 powder-based electrode for the electrooxidation of Glu.…”
Section: Acs Applied Materialsmentioning
confidence: 99%
“…In contrast, most of the existing cobalt-based catalysts that are used for non-enzymatic sensing of Glu require strong alkaline conditions. 23,39,41,42 Furthermore, while some other metal phosphate systems (e.g., Ni 3 (PO4) 2 -based materials 66 ) have shown greater sensitivity for glucose detection than our currently reported materials, the detection range was investigated below the typical glucose concentration of human blood (i.e., <1 mM), and measurements were also performed in strongly alkaline conditions (1 M NaOH solutions). Figure S8 shows the amperometric responsiveness of commercial Co 3 (PO 4 ) 2 powder-based electrode for the electrooxidation of Glu.…”
Section: Acs Applied Materialsmentioning
confidence: 99%
“…The value of the slope (log v vs log I pa ) can also be used to analyze the kinetic process of the electrochemical reaction and 0.5 was considered a typical diffusion-controlled process. 35,36 Therefore, both the results indicated that a diffusion-controlled process occurred on the Au@NiO-2 electrodes in the glucose oxidation reaction. The charge transfer coefficient (α) can be obtained by analyzing the Tafel plot of E p vs. log I.…”
Section: Resultsmentioning
confidence: 78%
“…After the rest, the human subject continued to exercise, the AlGaN/GaN HEMT was again exposed to sweat, and the concentrations of H + and K + increased again. The pH of the subject during the two indoor cycles was in the range of 4–6.8 , and the K + concentration was approximately 5 mM , which is in the normal physiological range. This experiment also verified that AlGaN/GaN HEMTs can be used for wearability.…”
Section: Resultsmentioning
confidence: 99%